Dari Kelas ke Lapangan: Dampak Mata Kuliah Kewirausahaan Terhadap Aktivitas Berwirausaha Mahasiswa Ekonomi - Wahyu Fajar Dhiyaul Haq; Ah. Ali Arifin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to describe and analyze how entrepreneurship courses influence the entrepreneurial activities of economics students. The background to this research arises from the increasing need to develop an entrepreneurial spirit during college, particularly due to increasingly fierce job competition and the demand for graduates to be able to create business opportunities. This study applies a descriptive qualitative method with data collection methods that include in-depth interviews, observation, and documentation of students who have taken entrepreneurship courses. The data analysis process is carried out through the steps of data reduction, data presentation, and drawing conclusions. The research findings show that practical learning experiences, such as assignments in developing business plans, business simulations, and field visits, have a significant influence on increasing students' motivation and courage to start a business. In addition, this course also fosters creative thinking patterns, improves problem-solving skills, and strengthens students' confidence in making business decisions. These findings confirm that entrepreneurship learning not only provides theoretical knowledge but also creates practical experiences that encourage students to participate in actual business activities. This research provides an important foundation for the development of a more practical entrepreneurship curriculum that focuses on hands-on experience.